Investigating the Impact of Creatine and Vitamin C Supplementation on Insulin Sensitivity and Glycated Hemoglobin Levels in Male Rabbits (مجلة الرازي الطبية, 2025)
Insulin resistance and impaired glucose metabolism are key features of metabolic disorders such as type 2 diabetes mellitus. Natural supplements such as creatine and ascorbic acid have shown potential in improving glycemic control through different biochemical mechanisms. This study aimed to evaluate the effects of creatine supplementation (CrS), ascorbic acid, and their combination on glucose metabolism, insulin sensitivity, and long-term glycemic control in male rabbits. Male rabbits were randomly assigned to four groups: control, creatine-treated, ascorbic acid-treated, and combination-treated. Fasting blood glucose, plasma insulin levels, homeostasis model assessment of insulin resistance (HOMA-IR), and glycated hemoglobin (HbA1c) were measured to assess metabolic status. Treatments were administered over a specific period, and data were analyzed using standard biochemical and statistical methods. Creatine supplementation resulted in a significant hypoglycemic effect and improved insulin sensitivity, with a notable reduction in HOMA-IR (0.85 ± 0.104) compared to the control group (1.12 ± 0.144). Ascorbic acid exerted a milder glucose-lowering effect but contributed to improved antioxidant defenses, potentially protecting pancreatic β-cells from oxidative damage. Plasma insulin levels did not significantly differ among groups (3.27 ± 0.356 to 4.00 ± 0.707 g/dL), suggesting enhanced insulin action rather than increased secretion. HbA1c levels were significantly reduced in all treatment groups, with the combination group achieving the lowest level (3.21 ± 0.43%), followed by creatine (3.8 ± 0.4%) and ascorbic acid (4.6 ± 0.45%). Creatine and ascorbic acid, individually and in combination, effectively improved markers of glucose metabolism in male rabbits. Creatine demonstrated a stronger effect in enhancing insulin sensitivity and lowering glucose, while ascorbic acid played a supportive role by reducing oxidative stress and preserving insulin function. These findings highlight the potential therapeutic value of combining antioxidant and creatine supplementation for managing insulin resistance and hyperglycemia.